Characterizing a complex buildup in the Pearl River Mouth Basin of the northern South China Sea: an interplay of carbonates and igneous rocks - Beichen Chen; Leyi Xu; Baojun Liu; Lili Zhang; Dong Xiao; Ya Gao; Ya Gao; Feng Wu; Xueqi Yang; Yaming Zou; Yongkun Ma; Yinglin Zhang (Frontiers in Marine Science)
Volcanic mounds and carbonate buildups share similar geometries, making their differentiation in seismic data a significant challenge. This challenge is further compounded in complex buildups composed of both multi-stage developed igneous rocks and biogenic carbonates. To address this gap, this study investigates a mixed carbonate-igneous buildup at the central of the Baiyun Sag in the northern South China Sea. By analyzing the lithofacies of the carbonates and igneous rocks, the morphological features and spatial distribution patterns corresponding to these sedimentary and volcanic facies were identified. Well-to-seismic calibration was used to delineate the stratigraphic units, and typical seismic profiles of the buildup were analyzed. Eight distinct seismic facies were identified for carbonates and igneous rocks. The evolution of the buildup is divided into three stages: (1) volcanic eruptions and carbonates development, (2) overflowing magma and reef shoal deposits, and (3) reef-bank deposition accompanied by igneous intrusion. We propose that volcanic rocks can be distinguished from carbonates by the temporal and spatial coupling of typical features: (a) surface volcanic rocks and subsurface intrusive bodies are inseparable, with igneous rocks identifiable through faults and volcanic conduits; (b) carbonates typically display symmetrical structures on both sides of the highland and exhibit better stratification away from igneous activity; (c) carbonates generally show a convex clinoform and steep slope at the platform margin, while volcanic mounds exhibit concave gentle slopes. Furthermore, the analysis of high-quality reservoir development within the complex buildups is instrumental for advancing oil and gas exploration in volcanic seamounts and carbonate buildups.